Kinetic Study on p-Nitrophenyl Picolinate Hydrolysis Promoted by the Complex Bis(O, O′-di(2-Benzyl)Dithiophosphato)Nickel(II). (5th August 2009) - Xie, Jiaqing; Xie, Bin; Feng, Fa-Mei; Zou, Li-Ke; Feng, Jian-Shen
The complex Ni[S2P(OCH2Ph)2]2 (MR) was synthesised and characterised by elemental analysis, IR spectroscopy and 1H NMR spectroscopy. The hydrolysis of p-nitrophenyl picolinate (PNPP) as promoted by this complex was investigated by the UV-vis method, the results showing that MR acts as a very efficient catalyst. The specific absorption spectra of the hydrolytic reaction systems indicated that the key intermediate, made up of PNPP and MR was formed during reaction. Based on these spectra, a mechanism for the catalytic hydrolysis of PNPP has been proposed and a kinetic mathematical model established.